The Impact of the Information and Electronic Transaction Law (UU ITE) on Legal and Social Changes in Society - Nurkholim Nurkholim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In principle, the improvement of information and technology systems that are currently developing in the global community, turns out to have a very significant impact on the social and legal system in Indonesia as a whole. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the existence of the ITE Law as a new legal product that applies in Indonesia is actually enough to bring changes in the positive legal justice system in Indonesia, although in principle the use of this law is still considered taboo and has not had a tremendous impact on various actions related to the use of information and communication in a very broad scope, advances in information and communication technology also have an impact on the development of legal interactions and social interactions. In addition to making a positive contribution to users, this information technology media also creates a negative side. For this reason, through law number 11 of 2008 concerning information and electronic transactions, various policies and legal justice can be realized evenly and can provide the fairest legal protection for all Indonesian people.